A comparative study on the removal efficiency of metal ions (Cu2+, Ni2+, and Pb2+) using sugarcane bagasse-derived ZnCl2-activated carbon by the response surface methodology. Issue 1 (March 2017) - Van Tran, Thuan; Bui, Quynh Thi Phuong; Nguyen, Trinh Duy; Le, Nhan Thi Hong; Bach, Long Giang
In the present article, the optimization of removal of Cu 2+, Ni 2+, and Pb 2+ using sugarcane-based activated carbon was studied. The activated carbon synthesized from low-cost sugarcane bagasse via ZnCl2 activation process was found to possess surprisingly high surface area (>1500 m 2 /g). In adsorption study, the individual and interactive effects of three critical parameters including initial concentration, pH of solution, and activated carbon dosage on removal efficiency of Cu 2+, Ni 2+, and Pb 2+ were assessed by applying the response surface methodology combined with central composite design. The established second-order polynomial regression models provided an excellent interpretation of experimental data with acceptable coefficients of determination ( R 2 ) and analysis of variance demonstrated statistical significance of the model terms. In the examined region, the predicted maximum removal efficiency and adsorption capacity were found in the order: Ni 2+ (66.4%, 2.99 mg/g) < Cu 2+ (90%, 13.24 mg/g) < Pb 2+ (99.9%, 19.3 mg/g), which were also confirmed in the verification experiments.